Indigegogy An Invitation to Learning in a Relational Way - Wilson, Stan (Wissenschaftliche Buchgesellschaft (wbg), 2021)
Indigegogy stands for "Indigenous Pedagogy". It is coined by the Cree Scholar Stan Wilson who advocates for culturally sensitive concepts of teaching and learning. The book unfolds a dialogue between him and the German philosopher Barbara Schellhammer inviting its readers into a process of relational learning.